P04.13 EXPRESSION OF PLURIPOTENCY STEMNESS GENES IN HUMAN GLIOMAS OF DIFFERENT TUMOR GRADES BEFORE AND AFTER CHEMOTHERAPY - Dreher, L. (Oxford University Press, 2014)
OBJECTIVE: Following the concept of glioma stem-like cells being the crucial reservoir for self-renewal, differentiation and proliferation of malignant brain tumors and escaping from adjuvant therapy numerous efforts have been made to exactly characterize them. However, several functional assays and analysis of surface markers to clearly identify this subgroup have led to insufficient and controversial results so far. Therefore we analyzed the expression levels of a bunch of potential markers of glioma stem-like cells in human glioma samples of different WHO grades and different treatment. We aimed not only to identify an adequate specific marker for stemness in human gliomas but also to gain insight into expression changes with increasing tumor grade and effects of chemotherapy on cancer stem cell activity. METHODS: cDNA was synthesized from mRNA of 80 snap frozen tumor samples from patients with gliomas of different tumor grades and pre-treatment (WHO grade II, III, secondary glioblastoma ± chemotherapy, primary glioblastoma ± chemotherapy, peritumoral tissue) and from 5 cell lines (U87, Gl36, HES2 (human embryonic stem cells), NPC (neuronal progenitor cells), hDF (human dermal fibroblasts)). Using quantitative real-time PCR relative expression levels of cMyc, Klf4, Nanog, Nestin, Oct4, and Sox2 were analyzed. Quantitative data were normalized in relation to the housekeeping gene SDHA. Results are depicted in mean ± SEM. RESULTS: The expression of Sox2 in all tested tumor groups was higher than in the control peritumoral tissue (2.10 ± 0.72). Interestingly highest expression levels were seen in WHO grade II (8.37 ± 1.60) and grade III (9.80 ± 2.20) tumor groups. cMyc, Nanog and Nestin expression were generally low compared to other tested genes in all tumor samples including control tissue, without any significant differences between the tumor grades and pre-treatment. Oct4 expression was high in all tested tumor groups (mean ranging from 7.5-57.77) compared to other genes. Remarkably Klf4 was lower expressed in two of the tested tumor groups compared to control tissue. CONCLUSIONS: We here provide expression profiles of different stemness genes in human tumors of different grades and treatment on genetic level. Interestingly, the transcription factor Sox2 seems to play a role especially in gliomagenesis as it is overexpressed in lower grade gliomas. At present we are completing our findings with biochemical methods (Western blot analysis).